Personality Traits as Predictors of Academic and Work Engagement in a Sample of Nursing Students and Professionals - Maja Kućar; Andreja Brajša-Žganec; Marijana Neuberg (Nursing Reports)
Background/Objectives: Academic engagement (AE) and work engagement (WE) are important indicators of performance and well-being in educational and occupational settings. Although these constructs are well researched independently, few studies have examined them concurrently among individuals navigating both academic and professional demands. Nursing students who are simultaneously employed as nurses represent a unique and under-researched population in this context. Understanding how personality traits influence both AE and WE in this dual-role group may offer insights relevant for academic success and well-being in healthcare settings. Methods: The sample consisted of 230 nursing students from a public university in Croatia who were also working as nurses. This study employed a repeated cross-sectional descriptive predictive research design (2022–2025). The participants completed questionnaires (UWES-9, UWES-S-9, and IPIP-15) during their university lectures. Results: The analysis yielded two personality clusters (adaptive—lower levels of neuroticism and higher levels of the other personality traits and maladaptive—the opposite). The participants in the adaptive cluster had higher levels of WE and AE. Regression analysis revealed that conscientiousness was a significant predictor for WE and AE, whereas agreeableness was a significant predictor for only WE. Conclusions: The findings highlight the importance of personality traits when addressing AE and WE, and fostering traits such as conscientiousness and agreeableness may enhance positive work and academic outcomes. Personality traits showed similar patterns of association with both AE and WE, indicating that dispositional factors may play a more crucial role in WE and AE than external influences.